Medicinal herbals with antiplatelet properties benefit in coronary atherothrombotic diseases - Mohd Nor, Nurul Huda; Othman, Fauziah; Mohd Tohit, Eusni Rahayu; Md Noor, Sabariah (Hindawi Publishing Corporation, 2016)
Coronary atherothrombotic diseases such as coronary artery disease, peripheral vascular disease, cerebrovascular disease, and heart failure are the serious concerns of the thrombus formed in blood vessels. Anticoagulant and antiplatelet drugs are the cornerstones of the management of these diseases. To prevent the recurrence of these diseases, double antiplatelet drugs such as aspirin and clopidogrel has been the standard management in most hospitals. However, aspirin resistance and clopidogrel inefficient effects due to noncompliance with double drugs regimen can cause a sinister effect on patients. Medicinal plants serve as a greater resource for new medication and their potential currently became a topic of interest to the researchers all over the world. Traditionally, certain herbs have been used as a treatment for heart diseases but have been investigated for their antiplatelet properties. This current review explained few traditional antithrombotic herbals and their antiplatelet properties in vitro and in vivo and this is to be deeply discussed in further research.